Relationship between soils and landscape units in the Pantanal ecosystem, in Brazil. - Cardoso, Evaldo Luis; Santos, Sandra Aparecida; Urbanetz, Catia; Filho, Amaury de Carvalho; Naime, Uebi Jorge; Silva, Marx Leandro Naves; Curi, Nilton (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the changes in soils and their chemical attributes under different landscape units in the Pantanal ecosystem, in the Nhecolândia subregion, in the state of Mato Grosso do Sul, Brazil. The evaluated landscape units included: SF, semideciduous forest; CE, “cerradão”;CC, “cerrado”/“campo cerrado”; TPE, tropical open grassland with Elionurus muticus; TPA, tropical open grassland with Axonopus purpusii and Andropogon spp.; EP, edge of ponds; and TPL, temporary channels/lowlands. Soil profiles representative of each landscape unit were morphologically described, and chemicalattributes were determined in the depths of 0.00–0.05, 0.05–0.10, 0.10–0.15, and 0.15–0.20 m. The soils showed sandy texture, low soil organic matter content, and low cation and anion exchange capacity. The main difference between the evaluated soils was natural fertility, which was higher in the SF, particularly at the surface layers and at the horizons below 2-m depth. Soil chemical quality is able to discriminate the landscapeunits into three different groups: 1, SF; 2, CE; and 3, CC, TPE, TPA, EP, and TPL.
Keywords: wetland; floristic composition; environmental conservation; landscape funcioning; Pantanal of Nhecolândia; natural systems